Uterine dynamics, blood profiles, and electronic fetal monitoring of primiparous and multiparous bitches classified according to their weight - Lezama-García, Karina; Martínez-Burnes, Julio; Baqueiro-Espinosa, Uri; Villanueva-García, Dina; Olmos-Hernández, Adriana; Hernández-Ávalos, Ismael; Mora-Medina, Patricia; Domínguez-Oliva, Adriana; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2023)
Perinatal mortality occurs in all species. In dogs, mortality rates have been reported to range from five 5% to 35%. Electronic foetalfetal and uterine monitoring has recently been used in domestic animals to monitor the mother and newborn before and during parturition. In this way, the foetalfetal heart rate and uterine dynamics can be monitored. This study evaluated the uterine dynamics in of bitches with different weights and parity numbers. Ninety-six bitches and their 476 puppies were allocated divided ininto four experimental groups of containing 24 individuals each (12 primiparous bitches and 12 multiparous damsbitches), according tothe to the body weight of the bitches: G1 (4-8 kg), G2 (8.1-16 kg), G3 (16.1 to 32 kg), and G4 (32.1 to 39.6 kg). The foetalfetal heart rate decelerations (DIP dip 2 patterns) decelerations, uterine dynamics, and bitches' blood profiles were evaluated, including levels of glucose, lactate, pCO2, pO2, pH, HCO3 − , and Ca ++ . It was observed that tThe dam'sdam weight can affect the vitality of newborns and the uterine dynamics of bitches, showing with differences in the frequency, intensity, and duration ofmyometrialof myometrial contractions. The expulsion interval between puppies was longestr in the lightest primiparous bitches with low weight and shortestr in the heaviest multiparous bitches with high weight. The expulsion This is a provisional file, not the final typeset article phase'sphase duration interval and the number of stillbornswere stillborn females were greater higher in the heavier primiparous femalesbitches with high weight. Newborn male puppies were significantly heavier than newborn females.